2019
DOI: 10.1186/s42825-019-0007-7
|View full text |Cite
|
Sign up to set email alerts
|

Factors affecting mass transfer of protease in pelt during enzymatic bating process

Abstract: Bating pelt with protease is an important process, which removes unwanted non-collagenous proteins from the pelt and moderately disperse hide collagen network. However, the grain surface, may be excessively hydrolyzed during bating due to the longer retention time of protease in the grain than in the middle layer caused by the low mass transfer rate of protease in pelt. Here, the effects of protease dosage, common auxiliaries and molecular weight of protease on protease transfer during bating were investigated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 26 publications
0
6
0
Order By: Relevance
“…It is necessary and important for chemicals to penetrate into the leather and distribute evenly; in this way, the relevant procedures will be carried out favorably and leather will have better performances. 23 In normal chrome tanning process, pickled pelt is tanned under low pH to allow the chrome tanning agent to penetrate at rst, and then alkali is added to increase the pH of the tanning system to enhance the combination between collagen and chromium. Previous studies have demonstrated that stronger tanning effect was obtained during hide powder chrome tanning process.…”
Section: Introductionmentioning
confidence: 99%
“…It is necessary and important for chemicals to penetrate into the leather and distribute evenly; in this way, the relevant procedures will be carried out favorably and leather will have better performances. 23 In normal chrome tanning process, pickled pelt is tanned under low pH to allow the chrome tanning agent to penetrate at rst, and then alkali is added to increase the pH of the tanning system to enhance the combination between collagen and chromium. Previous studies have demonstrated that stronger tanning effect was obtained during hide powder chrome tanning process.…”
Section: Introductionmentioning
confidence: 99%
“…The functional unit of three tanning systems in the present assessment is defined as processing 1000 kg of pickled pelt because the pickled pelt is not only a raw material for tanning but also an important intermediate product that can be traded in the leather industry. Modern leather processing, as shown in Figure , involves raw hide preservation, beamhouse (removal of noncollagen components from hides and dispersion of collagen fibers to obtain the pickled cow hide), tanning (conversion of a raw hide into durable leather by cross-linking collagen fibers with a tanning agent), , post-tanning (endowing leather with satisfactory physical and organoleptic properties using retanning agents, dyestuffs, and fatliquors), , finishing (giving leather artistic beauty and special functions such as waterproof and dustproof), packaging, and transportation. The main differences in the inputs and the outputs of various tanning systems are from tanning and post-tanning stages rather than the other stages (see Figure S3).…”
Section: Methodsmentioning
confidence: 99%
“…In addition, the samples retanned with ME were cut along the vertical direction, and the vertical sections were directly observed by a stereo microscope (SZX12, Olympus, Japan) to locate ME in leather. The fluorescence and stereo micrographs were processed by Image J software to calculate the relative content and the penetration rate of fluorescent retanning agent in leather [22].…”
Section: Observation Of Retanning Agents Distribution In Leathermentioning
confidence: 99%